Chinese Poetry in Times of Mind, Mayhem and Money - van Crevel, M. (Asian Studies, 2008)
Chinese Poetry in Times of Mind, Mayhem and Money is a groundbreaking study covering a range of contemporary authors and issues, from Haizi to Yin Lichuan and from poetic rhythm to exile-bashing. Its rigorous scholarship, literary sensitivity and lively style make it eminently fit for classroom use.